Hubungan Dukungan Keluarga terhadap Kepatuhan Minum Obat pada Penderita Tuberkulosis: Relationship of Family Support to Drug Compliance in Tuberculosis Patients - Mantovani, Muhamad Rizal; Ningsih, Fitriani; Tambunan, Lensi Natalia (Jurnal Surya Medika (JSM), 2022)
Tuberculosis (TBC) which is also often called "pulmonary spots" is a chronic respiratory disorder caused by infection with the bacterium Mycobacterium tuberculosis. The phenomenon that is obtained is that there are still tuberculosis patients who do not comply with taking OAT drugs. Patients who do not comply are caused by a lack of family support for tuberculosis patients and the potential risk of drug resistance in tuberculosis patients. This study aims to determine the relationship between family support and Drug Compliance in Tuberculosis Patients based on data through the literature review method. Using the literature review method. Journal searches use an academic database, namely Google Scholar, which was published in 2017-2020 using Indonesian and English. Study design Cross-sectional. Obtained 6 research results according to the inclusion criteria. The research sample averaged 26-83 respondents. There are 5 journals that state that there is a relationship between family support and medication adherence in tuberculosis patients which shows a p-value <0.05, while 1 journal states that there is no relationship between family support and medication adherence in tuberculosis patients. Good family support will affect the regular treatment of tuberculosis patients which is expected to help the success of tuberculosis patients to recover. The higher the family support for tuberculosis, the better the adherence to taking TB medication and shows that there is a very significant relationship between family support and medication adherence in patients with tuberculosis.